2014
DOI: 10.1111/pan.12489
|View full text |Cite
|
Sign up to set email alerts
|

Pain management following major intracranial surgery in pediatric patients: a prospective cohort study in three academic children's hospitals

Abstract: Introduction Pain management following major intracranial surgery is often limited by a presumed lack of need and a concern that opioids will adversely affect postoperative outcome and interfere with the neurologic examination. Nevertheless, evidence in adults is accumulating that these patients suffer moderate to severe pain and this pain is often under-treated. The purpose of this prospective, clinical observational cohort study was to assess the incidence of pain, prescribed analgesics, methods of analgesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 27 publications
0
23
0
7
Order By: Relevance
“… 10 Therefore, it has been historically reasoned that patients’ exposure to the risks of opioid administration should be minimized given the widely presumed idea that intense pain is not experienced following intracranial procedures, a belief reinforced by the fact that surgical procedures on the brain parenchyma in itself do not cause pain. 11 …”
Section: Introductionmentioning
confidence: 99%
“… 10 Therefore, it has been historically reasoned that patients’ exposure to the risks of opioid administration should be minimized given the widely presumed idea that intense pain is not experienced following intracranial procedures, a belief reinforced by the fact that surgical procedures on the brain parenchyma in itself do not cause pain. 11 …”
Section: Introductionmentioning
confidence: 99%
“…The main analgesic methods advocated in current studies are multimodal analgesia and PCIA or NCIA analgesia 5,7 . Maxwell et al 7 have demonstrated that PCIA or NCIA analgesia is an effective analgesia with a low incidence of opioid-related side effects; although it should be noted that the analgesic pump settings in their study were not standardized. Chiaretti 21 found PCIA with fentanyl plus midazolam could effectively relieve postoperative pain in pediatric neurosurgery.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease of 20% will be considered a minimal clinically important difference. According to Maxwell's article [30] and our experience, 54 subjects per group will be necessary with a two-sided α level of 0.017 (0.05/3) and 80% power. Considering a 10% rate of loss to follow-up, it would be necessary to include 60 participants per group (total: 180 participants).…”
Section: Sample Sizementioning
confidence: 99%